Pulmonary hypertension associated with neurofibromatosis type 2 - Taniguchi, Hirohisa (Pulm Circ, 2021)
Although precapillary pulmonary hypertension is a rare but severe complication of patients with neurofibromatosis type 1 (NF1), its association with NF2 remains unknown. Herein, we report a case of a 44-year-old woman who was initially diagnosed with idiopathic pulmonary arterial hypertension and treated with pulmonary arterial hypertension-specific combination therapy. However, a careful assessment for a relevant family history of the disease and genetic testing reveal that this patient had a mutation in the NF2 gene. Using immunofluorescence and Western blotting, we demonstrated a decrease in endothelial NF2 protein in lungs from idiopathic pulmonary arterial hypertension patients compared to control lungs, suggesting a potential role of NF2 in pulmonary arterial hypertension development. To our knowledge, this is the first time that precapillary pulmonary hypertension has been described in a patient with NF2. The altered endothelial NF2 expression pattern in pulmonary arterial hypertension lungs should stimulate work to better understand how NF2 is contributing to the pulmonary vascular remodelling associated to these severe life-threatening conditions.